Peningkatkan Kecerdasan Naturalis Anak Dengan Menggunakan Pendekatan Saintifik di TK Negeri Satu Atap Unit X Kecamatan Waelata Kabupaten Buru - Ita Aprilia; Lambertus J. Lokollo (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the use of a scientific approach to increase the naturalist intelligence of children in Unit X One-Stop Public Kindergarten, Waelata District, Buru Regency. This study used a scientific approach using the classroom action research method (CAR), which consisted of 2 cycles with 19 research subjects with an average age of 5-6 years. The naturalist intelligence of children referred to in this study includes the following aspects 1) Children can observe plant species. 2) Children can ask the names and uses of the types of plants. 3) Children are able to distinguish the characteristics and benefits of plants. 4) Children can communicate and be able to retell. The results showed that the results obtained were 42% in cycle I and 79% in cycle II. The conclusion in this study is that the method of increasing children's naturalist intelligence using a scientific approach can improve children's naturalist intelligence in Unit X One-Roof State Kindergarten, Waelata District, Buru Regency.